In Her Own Words : Conversations with Composers in the United States - Kelly, Jennifer (Musician) (Book collections on Project MUSE., 2013)
This collection of interviews with twenty-five accomplished female composers explores the work, experiences, compositional approaches, and musical intentions of a diverse group of creative individuals. With personal anecdotes and sometimes surprising intimacy and humor, these wide-ranging conversations represent the diversity of women composing music in the United States from the mid-twentieth century into the twenty-first. The female composers interviewed in this text work in a variety of genres, including classical, jazz, multimedia, or collaborative forms for the stage, film, and video games. Their interviews illuminate questions about the status of women composers in America, the role of women in musical performance and education, the creative process and inspiration, the experiences and qualities that contemporary composers bring to their craft, and balancing creative and personal lives.